High-Frequency Ultrasonography—Possibilities and Perspectives of the Use of 20 MHz in Teledermatology - Polańska, Adriana; Jenerowicz, Dorota; Paszyńska, Elżbieta; Żaba, Ryszard; Adamski, Zygmunt; Dańczak-Pazdrowska, Aleksandra (Frontiers in Medicine, 2021)
High frequency ultrasonography (HF-USG) is a non-invasive and in-vivo method of visualization of the skin and upper part of subcutaneous tissue which is based on ultrasounds above 20 MHz. Although initially HF-USG was introduced to measure skin thickness, currently it gained widespread acceptance in dermatooncology, especially when is used to determine the margins of skin tumors. Moreover its application in different fields of dermatology is known, particularly as a rapidly evolving method in the objective evaluation of the severity of the various chronic skin diseases. Among different specialties, teledermatology belongs to leading and constantly developing areas of successful telemedicine application. Various skin conditions are visible to human eye, which makes them particularly suitable to telemedicine. However, HF-USG enables specialists to look into deeper skin layers, thus extending diagnostic options. On the other hand, teledermatology gives the possibility of sending images for consultation and facilitates the therapeutic decision as HF-USG can be used in asynchronous store and forward manner. It seems that HF-USG and teledermatology may be regarded as a truly matched pair. The aim of this work is to present current applications of 20 MHz ultrasonography in dermatology, including skin neoplasms and chronic skin diseases. Moreover the authors aimed to analyze possibilities of HF-USG use as a valuable tool in teledermatology, especially in diagnosing and monitoring patients suffering from long-lasting skin conditions.